Simpozijska vprašanja in Plutarhov makrotekst moškega prijateljstva - Sunčič, Maja (Monitor ISH, 2007)
The paper examines the difference between the topics of friendly discussions at symposia, treated by Plutarch in the nine books of his Table- Talk, and those addressed in his various treatises on the so-called popular morality. The two approaches to friendship seem to differ in their perception of the good, pleasant and profitable: while the symposiac discussions are pleasant and undisturbing, thus generating and strengthening friendship among the men drinking wine, those tackling the subjects of popular morality are more sombre, often unpleasant and disturbing. Both approaches are considered in the context of Plutarch's "workbook" on friendship, proposing an answer to the question "How to be a good friend".
Keywords: Plutarchus, ok.46-ok.120; philosophy; filozofija; ethics; etika; vsakdanje življenje; vsakdanja morala; prijateljstvo; man; moški